Collateral Consequences, Genetic Surveillance, and the New Biopolitics of Race - Roberts, Dorothy E. (2011)
This Article is part of a Howard Law Journal Symposium on “Collateral Consequences: Who Really Pays the Price for Criminal Justice?,” as well as my larger book project, Fatal Invention: How Science, Politics, and Big Business Re-create Race in the Twenty-First Century (The New Press, 2011). It considers state and federal government expansion of genetic surveillance as a collateral consequence of a criminal record in the context of a new biopolitics of race in America. Part I reviews the expansion of DNA data banking by states and the federal government, extending the collateral impact of a criminal record—in the form of becoming a permanent suspect—to growing categories of people. Part II argues that the benefits of this genetic surveillance in terms of crime detection, exonerations of innocent inmates, and public safety do not outweigh the unmerited collateral penalty of state invasion of individuals’ privacy and the larger harms to democracy. These harms are exacerbated by the disproportionate collection of DNA from African Americans as a result of deep racial biases in law enforcement. Part III explains why DNA databases reflect and help to perpetuate an oppressive system of criminal justice. Finally, Part IV elaborates the racial harms that are caused by genetic surveillance that targets large numbers of African Americans, putting into practice deep-seated stereotypes about blacks’ inherent criminality. Far from correcting racial bias in law enforcement, the state’s use of DNA to designate millions of permanent suspects reinforces the roots of racial injustice